Enhancing indigenous livestock production towards improving livelihoods among small-scale farmers in KwaZulu-Natal Province, South Africa - Nontu, Yanga; Ndwandwe, Nkosingimele; Dumisa, Bonguyise Mzwandile; Msane, Zole Nqobile; Dlamini, Sibusisiwe Nonkosi (Frontiers in Sustainable Food Systems, 2025)
Income security is a global concern threatening the livelihood of farmers. To ensure that the livelihoods of farmers are maintained, small-scale indigenous livestock farming serves as a solution to this issue. To investigate the income contribution of producing indigenous livestock towards small-scale farming households in uMhlathuze Municipality, this study was conducted. It randomly collected primary data from 60 small-scale indigenous livestock farmers, following a cross-sectional design with a quantitative approach. Findings from this study reveal that most small-scale indigenous livestock farmers in this area are predominantly middle-aged to older individuals, who are mostly single, male, and unemployed with no educational background. Indigenous livestock farmed include chicken, goats, cattle, and sheep. However, these farmers lack services such as extension, credit, infrastructure, markets, and veterinary services, which significantly impact production. Moreover, factors including age, education, household size, employment status, number of households employed, access to veterinary and extension services, theft, and diseases were found to be significant towards the households’ income security. This study, therefore, encourages the adoption of indigenous livestock farming to sustain household income and preserve indigenous knowledge. Also, services such as extension, credit, infrastructure, markets, and veterinary services should be enhanced to improve farmer production and participation in markets.